Trade, inequality, and the size of the welfare state - Miriam Kohl (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
This paper investigates the effects of international trade in a general equilibrium model with heterogeneous firms where a welfare state redistributes income. We look at a very stylised progressive non-distortionary redistribution scheme. We show that for a given tax rate international trade increases income per capita, but also leads to higher income inequality. Two aspects of income inequality are examined. First, inter-group inequality between managers and workers is considered. Second, intra-group inequality within the group of managers is investigated. For a given tax rate the size of the welfare state and therefore the transfer per capita increases when going from autarky to trade. This second-round effect counteracts the primary increase in inequality, yet cannot outweigh it. Since the redistribution scheme is non-distortionary, it is possible to decrease trade-induced inequality by increasing the tax rate without jeopardising the gains from trade.
urn:nbn:de:bsz:14-qucosa-217393
Keywords: D31; F12; F16; H24; H25; 330; International trade; Income inequality; Redistribution; Heterogeneous firms